Recent progress of transparent conductive electrodes in the construction of efficient flexible organic solar cells. (1st December 2021) - Qiao, Fen; Chu, Huaqiang; Xie, Yi; Weng, Zhankun
Summary: Flexible transparent conducting electrodes (F‐TCEs) are an important part of a flexible solar cell. The performance of the F‐TCEs is very important for the transmission of light and charge. Therefore, the selection of appropriate characteristics of F‐TCES, especially electrical conductivity, light transmittance, and mechanical flexibility, is essential for fabricating solar cells with high performance. This article reviewed the latest development of F‐TCEs and the structural design of flexible solar cells, compared and analyzed the preparation methods, advantages, and disadvantages of several different F‐TCEs, such as metal oxides, metals, carbon materials, polymers, and their composites. Based on different solar cell structures and flexible substrate types, the measures to obtain high transmittance, low resistance, etc., were emphatically discussed to obtain F‐TCEs with excellent performance. In order to make up for the shortcomings of single electrode materials, the current development of composite F‐TCEs electrodes was discussed and analyzed. Finally, the challenges faced by F‐TCEs and future development direction were prospected, providing a reference for the design of future intelligent photovoltaic systems. Abstract : Around the structure design of flexible solar cells and the development of new transparent conductive electrodes, metal oxides, metals, carbon materials, polymers, and the composite materials were designed successively to obtain flexible transparent conductive electrodes with high conductivity, high transmission, and low surface roughness.